DIDACTIC MODEL BASED ON PRINCIPLES OF CRITICAL THINKING - Kazuša, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In Rīga Stradiņš University chemistry study process is developed by researching different pedagogical approaches and didactic models and their application methods in order to filter out the least effective ones. The aim of this research is the development of a didactic model of the medical chemistry course. As a result of this research, it was concluded that the most suitable didactic model is the one based on principles of critical thinking. Critical thinking principles behind this didactic model are purposefulness, information selection and analysis, critical reading and note-making, fundamental regularity spotting and awareness of one's own knowledge limitations. These principles raise their level of individual work culture by emphasizing responsibility for their choices and decisions are taken and also develop dialogue culture and tolerant attitude towards others. Suitability of methods based on critical thinking principles and their combinations depend on reachable goals. Reading, lectures, and the use of online resources are effective for obtaining knowledge, solving problems and involving students in the cognition process but are less suitable for developing skills and gaining experience. Discussions and practical exercises, on the other hand, are suitable for gaining study experience and developing skills and reflection. By mastering critical thinking principles, students learn to understand the specific situation from different aspects, to generalize and to carry over understanding from familiar situations to new.